A trapdoor spider, Latouchia typica (Araneae: Halonoproctidae), uses vibrational cues as a trigger for predatory behavior. Issue 4 (21st November 2022) - Nakamura, Shoyo; Mukai, Hiromi; Tokuda, Makoto
Abstract: Spiders are one of the most dominant predators in terrestrial ecosystems. Although cues triggering predatory behavior in web‐building and wandering spiders are well investigated, studies concerning burrowing species, the most ancestral group of spiders, are relatively limited. To clarify critical cues affecting the predatory behavior in burrowing species, we conducted vibration‐reducing experiments with the trapdoor spider Latouchia typica (Araneae: Halonoproctidae) and nymphs of the speckled cockroach, Nauphoeta cinerea (Blattodea: Blaberidae), as prey. Spiders achieved a high success rate of prey capture even when blinded (with paint on the eyes). However, the use of a rubber mat to reduce vibrations significantly decreased predation success rate. In addition, the presence or absence of the blindfold did not affect the predation rates under the reducing vibration condition. These results indicate that substrate vibrations emitted from prey are critically important to trigger the predatory behavior in L. typica, but visual and chemical stimuli are not used even in the case when vibration cues are unavailable. This is the first study to use vibration‐reducing experiments to experimentally demonstrate the critical cues for predation in trapdoor spiders.